PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT. SUCOFINDO, Tbk MAKASSAR - Fitriany Fitriany (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
This research aimed to find out the of service quality at PT. Sucofindo, Tbk.of Makassar involving tangible, reliability, empathy, responsiveness, assurance dimensions and the influence of the service quality on customers’ satisfaction at PT. Sucofindo, Tbk. of Makassar. The data in this research consisted of quantitative and qualitative data. They were obtained through observation and questionnaire to 100 respondents who were the customers of PT. Sucofindo, Tbk. of Makassar. They were then analyzed using multiple linear regression, F-test, and test. The formulated hypothesis was also explained to see to what extent it was proved empirically. The results show that both simultaneously and partially service dimension consisting of tangible, empathy, reliability, responsiveness, and Assurance have a significant influence on the customers’ satisfaction at PT. Sucofindo, Tbk. of Makassar Reliability dimension has dominant influence on the customers’ satisfaction at PT. Sucofindo, Tbk. of Makassar. The dominant influence of this variable is determined by the indicators forming it, that is, capability, acceptance process, trchnical knowledge/skill possessed by the employess, the quickness of certification, the accuracy/quickness of quality test, process, and procedure. All of these indicators are considered to be very good and reliable.